Pre-service early childhood teachers' views on STEM education and their STEM teaching practices - Ciftci, Ayse; Topcu, Mustafa Sami; Foulk, Jaimie A. (Routledge Journals, Taylor & Francis Ltd, 2020)
Background STEM education integrates the disciplines of science, technology, engineering and mathematics. Relevant research emphasizes a strong relationship among characteristics of STEM education and the early childhood period, such as investigation, exploration and observation, communication and playing. To support children in discovering STEM fields and concepts in this early childhood period of rapid learning and development, early childhood educators should prioritize the integration of STEM education into the early childhood curriculum. Purpose This research aims to explore pre-service early childhood teachers' views on STEM education and their STEM teaching practices. Sample The research group consisted of 91 pre-service early childhood teachers studying at two universities in Istanbul, Turkey. Design and methods An open-ended questionnaire and STEM integrated lesson plans were used as data collection tools. Data were analyzed through content analysis and descriptive analysis. Results As a result, the themes of 'Contributions of STEM Education', 'Why STEM Education is Suitable for Early Childhood Education' and 'How to Bring STEM Education into Early Childhood Education' were obtained based on pre-service early childhood teachers' views. The categories related to these themes are provided in detail in the 'Results' section. In addition, it was concluded that a majority of the pre-service early childhood teachers prepared and implemented STEM integrated lesson plans successfully. Conclusion The present research contributes to the literature related to STEM education in early childhood education, particularly regarding professional development of pre-service early childhood teachers.
Keywords: STEM education; STEM teaching practices; pre-service early childhood teachers; views on STEM education; early childhood education